Gambaran Pola Konsumsi Lauk Hewani dan Status Gizi Siswi di SMP Negeri 9 Kendari - Febriana Muchtar; Hartati Bahar (Jurnal Kendari Kesehatan Masyarakat, 2024)
Indonesia continues to face a triple burden of nutritional challenges, including stunting, wasting, and obesity. Adolescents represent a nutritionally vulnerable population due to factors such as lifestyle choices, inadequate nutritional knowledge, and unhealthy dietary habits. These factors contribute to nutritional problems such as anemia, chronic energy deficiency (CED), and obesity. Objective: This study aims to analyze the consumption patterns of animal-based side dishes and assess the nutritional status of female students at SMP Negeri 9 Kendari. Methodology: This descriptive study included a total population of 614 female students, with a sample of 35 selected using a cluster random sampling method. Data were collected from one randomly selected class. Results: Findings revealed that 62.8% of the respondents were classified as thin or severely thin, 28.6% had normal nutritional status, and 8.6% were obese. The consumption pattern of animal-based side dishes showed that most types were rarely consumed, with fish being the most commonly consumed source of animal protein, reported by 48.5% of respondents (17 students). Conclusion: The study concludes that the consumption of animal protein among the respondents is considerably low, and the majority of the students exhibit nutritional statuses classified as thin or severely thin (62.8%).